Differential Influence of Levodopa on Reward-Based Learning in Parkinson's Disease - Graef, Susanne; Biele, Guido; Krugel, Lea K.; Marzinzik, Frank; Wahl, Michael; Wotka, Johann; Klostermann, Fabian; Heekeren, Hauke R. (Frontiers in Human Neuroscience, 2010)
The mesocorticolimbic dopamine (DA) system linking the dopaminergic midbrain to the prefrontal cortex and subcortical striatum has been shown to be sensitive to reinforcement in animals and humans. Within this system, coexistent segregated striato-frontal circuits have been linked to different functions. In the present study, we tested patients with Parkinson's disease (PD), a neurodegenerative disorder characterized by dopaminergic cell loss, on two reward-based learning tasks assumed to differentially involve dorsal and ventral striato-frontal circuits. 15 non-depressed and non-demented PD patients on levodopa monotherapy were tested both on and off medication. Levodopa had beneficial effects on the performance on an instrumental learning task with constant stimulus-reward associations, hypothesized to rely on dorsal striato-frontal circuits. In contrast, performance on a reversal learning task with changing reward contingencies, relying on ventral striato-frontal structures, was better in the unmedicated state. These results are in line with the “overdose hypothesis” which assumes detrimental effects of dopaminergic medication on functions relying upon less affected regions in PD. This study demonstrates, in a within-subject design, a double dissociation of dopaminergic medication and performance on two reward-based learning tasks differing in regard to whether reward contingencies are constant or dynamic. There was no evidence for a dose effect of levodopa on reward-based behavior with the patients’ actual levodopa dose being uncorrelated to their performance on the reward-based learning tasks.